Evolution and structural diversification of PILS putative auxin carriers in plants - Feraru, Elena; Vosolsobě, Stanislav; Feraru, Mugurel I.; Petrášek, Jan; Kleine-Vehn, Jürgen (Frontiers in Plant Science, 2012)
The phytohormone auxin contributes to virtually every aspect of the plant development. The spatiotemporal distribution of auxin depends on a complex interplay between auxin metabolism and intercellular auxin transport. Intracellular auxin compartmentalization provides another link between auxin transport processes and auxin metabolism. The PIN-LIKES (PILS) putative auxin carriers localize to the endoplasmic reticulum (ER) and contribute to cellular auxin homeostasis. PILS proteins regulate intracellular auxin accumulation, the rate of auxin conjugation and subsequently, affect nuclear auxin signalling. Here, we investigate sequence diversification of the PILS family in Arabidopsis thaliana and provide insights into the evolution of these novel putative auxin carriers in plants. Our data suggest that PILS proteins are conserved throughout the plant lineage and expanded during higher plant evolution. PILS proteins diversified early during plant evolution into three clades. Besides the ancient Clade I encompassing non-land plant species, PILS proteins evolved into two clades. The diversification of Clade II and Clade III occurred already at the level of non-vascular plant evolution and, hence, both clades contain vascular and non-vascular plant species. Nevertheless, Clade III contains fewer non- and increased numbers of vascular plants, indicating higher importance of Clade III for vascular plant evolution. Notably, PILS proteins are distinct and appear evolutionarily older than the prominent PIN-FORMED auxin carriers. Moreover, we revealed particular PILS sequence divergence in Arabidopsis and assume that these alterations could contribute to distinct gene regulations and protein functions.